2004
DOI: 10.1093/molbev/msh089
|View full text |Cite
|
Sign up to set email alerts
|

Non-African Populations of Drosophila melanogaster Have a Unique Origin

Abstract: Drosophila melanogaster is widely used as a model in DNA variation studies. Patterns of polymorphism have, however, been affected by the history of this species, which is thought to have recently spread out of Africa to the rest of the world. We analyzed DNA sequence variation in 11 populations, including four continental African and seven non-African samples (including Madagascar), at four independent X-linked loci. Variation patterns at all four loci followed neutral expectations in all African populations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
99
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 56 publications
22
99
0
1
Order By: Relevance
“…Moreover, Pennsylvania and Tasmania Y chromosomes are nearly indistinguishable ( Figure 2 and Table 2). Consistent with several surveys of population differentiation showing considerable population structure in Asia (Hale and Singh 1991;Baudry et al 2004;Pool and Aquadro 2006;Schlötterer et al 2006), the Beijing Y chromosome is highly differentiated from the rest of the populations. There is no evidence of substructuring within the Beijing population on the Y chromosome ( Figure 2B).…”
Section: Population Structuresupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, Pennsylvania and Tasmania Y chromosomes are nearly indistinguishable ( Figure 2 and Table 2). Consistent with several surveys of population differentiation showing considerable population structure in Asia (Hale and Singh 1991;Baudry et al 2004;Pool and Aquadro 2006;Schlötterer et al 2006), the Beijing Y chromosome is highly differentiated from the rest of the populations. There is no evidence of substructuring within the Beijing population on the Y chromosome ( Figure 2B).…”
Section: Population Structuresupporting
confidence: 87%
“…There is no evidence of substructuring within the Beijing population on the Y chromosome ( Figure 2B). Outside of the clustering of Zimbabwe and Netherlands Y chromosomes, these results are consistent with the population structure of autosomal, X chromosomal, and mitochondrial loci from these or similar populations (Hale and Singh 1991;Baudry et al 2004;Haddrill et al 2005;Pool and Aquadro 2006;Schlötterer et al 2006). Genomic sequences from non-Y-linked loci exclude the possibility that the similarity of Netherlands and Zimbabwe Y chromosomes are explained by contamination in our fly lines (A.G. Clark, unpublished results).…”
Section: Population Structuresupporting
confidence: 84%
“…Our simulations predict a pooling effect over a wide range of migration rates, implying one way to test the null hypothesis of panmixia, i.e., that the genealogies of local samples are indistinguishable from those of scattered samples. Very few published studies have performed separate analyses of local population samples and the pooled sample consisting of several local samples, but many studies can, in principle, be used to test our predictions because several local samples have been included [Drosophila (Baudry et al 2004(Baudry et al , 2006Nolte and Schlö tterer 2008), humans (Marth et al 2004;Voight et al 2005;Keinan et al 2007;Garrigan et al 2007), and plants (Heuertz et al 2006;Pyhäjärvi et al 2007)]. Pool and Aquadro (2006) demonstrated the pooling effect in sub-Saharan D. melanogaster, as have several studies in plants (Ingvarsson 2005;Arunyawat et al 2007;Moeller et al 2007) and humans (e.g., Ptak and Przeworski 2002;Hammer et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Using an experimental design in which a consistent set of populations was sequenced for the same loci in both species, Baudry et al (2004Baudry et al ( , 2006) studied four Xlinked genes in African D. melanogaster (Kenya, Zimbabwe, Ivory Coast, and Niger) and D. simulans populations (Madagascar, Mayotte, Tanzania, and Kenya). Although it is not discussed by the authors, these studies revealed similar levels of variability in both species, even if only the most variable populations from the ''Eastern group'' (Madagascar, Mayotte, Tanzania, and Kenya) are considered for D. simulans:…”
Section: Discussionmentioning
confidence: 99%